ROLE OF SECONDARY METABOLITES ON BIOCONTROL POTENTIALITIES OF NATIVE RHIZOBACTERIAL ISOLATES AGAINST RHIZOCTONIA SOLANI - ADAM KAMEI; S. DUTTA; S. NANDI (The Bioscan, 2010)
Sixty two isolates of rhizobacteria were isolated from rhizosphere of rice crop, chilli, cabbage and potato collected from Gangetic Alluvial regions of West Bengal. Rhizobacterial isolates were evaluated in-vitro by dual culture method. Ten of which were found to be potent bioagents. The isolates were identified as Pseudomonas aerugenosa based on biochemical and molecular identification techniques. Studies revealed that the mycelial growth of R. solani was inhibited up to 1.9 (cm) by PTR-3 and were found to exhibit antagonism of over 68.9% which is followed by PCF-3(65.6%). Isolate PTR-3 having higher level of chitinolytic (17.2 pmol/s) and proteolytic (halo zone 2.9 cm) activity was highly effective against R. solani. Among the ten antagonistic rhizobacteria, highest level of salicylic acid(0.54), siderphore(3.9 μ mole benzoic acid /ml) and HCN production was noticed by PTR-1 isolate. Whereas, highest level of IAA(0.01039μg/ml) and Phosphate solubilisation(17.3μg/ml) activity were noticed by PTR-4 and PTR-3 isolates respectively. Extracellular enzymes activity of protease and chitinase were found to be highly and positively correlated with the ability to antagonize R solani. Step wise regression analysis revealed that the combination of biochemical variables chitinase and protease activity jointly contributing 98% of variability of antagonistic potentiality of rhizobacteria against, R. solani causing sheath blight disease of rice. These variables may be used as predictors of biocontrol potentiality of rhizobacteria against destructive soil-borne fungal pathogen Rhizoctonia solani.